The performance of government information technology officers in e-government policy implementation. - Nengovhela, Nthumeni R. (My University, 2013)
The purpose of this research is to investigate the performance of the Government Information Technology Officers (GITOs) in the implementation of e-government policy during the last decade. The CIOs in the South African public sector are referred to as GITOs, the position in government departments that was established by a Cabinet memorandum in the year 2000. By 2001, the South African government developed an e-government policy framework which presents the basis for implementation of e-government initiatives by several stakeholders including the GITOs. A qualitative study was undertaken based on the case study of four national departments to determine the performance of the GITOs in the implementation of this policy. The literature review has pointed out several hindrances to the implementation of e-government initiatives and critical success factors that are to be in place to ensure successful implementation. The findings identifies the barriers for the GITOs to implement the e-government policy to include, weak policy, lack of strategic leadership, critical ICT skills, infrastructure, uncoordinated funding and low levels of e-readiness by departments. The analysis categorised the factors into six themes, i.e. ICT governance framework, leadership, organisational structural arrangement, digital divide (infrastructure and access) and integration of services and systems. The analysis of the findings and lessons from the literature review constituted the basis for policy recommendations in the last chapter.
Keywords: Information technology; Public administration; e-government policy; ICT policy; South Africa